MERAWAT JIWA MENJAGA TRADISI : Dzikir Dan Amal Thariqah Qadiriyah Naqsabandiyah Dalam Rehabilitasi Korban NAPZA Sebagai Terapis Ala Islam Nusantara - Alhamuddin Alhamuddin (Sosial Budaya, 2015)
The spread of drugs in Indonesia today drastically increase, both in the big cities and in remote areas. The victims are not only the adults, but also children. Curriculum for rehabilitating drug abuse victims at Pondok Inabah VII developed on the basis of tasawwuf (mysticism) approach. Stage of curriculum implementation are as follows: (1) Takhalli, self-purify from sin that pollutes the soul, both physically and spiritually; (2) Tahalli, self-adorns with good behaviors, both physically and spiritually;  (3) Tajalli, results from both of takhalli and tahalli. Tajalli is ultimate purpose of rehabilitation. Furthermore, those three concepts are applied in three core activities; Mandi Taubat (a person who washes their body to cleans theirselves from sin), Shalat and dzhikr.  In addition, the role of guide also decisive during the process of healing.  Inabah Method is unique; as it does not use any chemical drugs or herbs. Alternatively, religion therapy is used in order to recover drug victim, both in terms of physical, mental, social and spirituall. For further researcher, it is suggested to investigate this issue more specific and comprehensive.